Stakeholder Analysis and Management for Promoting Small and Medium-Scale Vegetable Processing Technology in Nepal - Joshi, Prateek; Karn, Sanjeev Kumar; Koirala, Pramod (International Journal of Applied Sciences and Biotechnology, 2024)
This article explores the intricate landscape of stakeholder analysis and management within the framework of promoting small and medium-scale vegetable processing technology in Nepal. Given that agriculture engages a substantial 66% of the country's workforce, the escalating demand for vegetables has been met with challenges stemming from the lack of support for vegetable processing industries, resulting in food waste and financial setbacks for farmers. Addressing these issues, the article advocates for holistic backing and promotion of vegetable processing industries in Nepal. The methodology section delineates a mixed-methods approach for stakeholder analysis, employing documentary reviews, key informant interviews, and surveys to get information. It further explores the constitutional roles of different government levels and details the initiatives by the Ministry of Agriculture and Livestock Development (MoALD) and other government agencies in propelling food processing technology. The stakeholder analysis provides a detailed examination of both internal and external stakeholders, categorizing them based on their power and interest. The power/interest grid and influence mapping assist in prioritizing stakeholder engagement and managing their expectations effectively. The article concludes by asserting that effective stakeholder management is crucial for addressing the challenges and promoting the growth of vegetable processing industries in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 12(1): 19-28.